Production, Purification, Characterization And Application Of Organic Solvent Tolerant Lipase From Trichoderma Sp. Bw45 In Palm Oil Hydrolysis - Al-Limoun, Muhamad Odeh Atyeh (2010)

(untitled)
In order to establish a successful process of enzymatic hydrolysis of palm oil, for the production of palmitic acid and oleic acid, the following objectives have been designated: Screening for potential microorganisms producing a significant amount of extracellular organic solvent tolerant lipase from indigenous soil samples, optimization of the physicochemical parameters required to achieve maximum lipase production in shake flask system, purification of the enzyme using aqueous two phase system coupled with Sephadex G-75 gel filtration, characterization of the pure enzyme properties and application of the crude lipase preparation in palm oil hydrolysis for the production of palmitic and oleic acids.